Power: its development and dynamics of young students during their studies at university. - Zyankin A.M. (Fizičeskoe Vospitanie Studentov, 2011)
The dynamics of the level of force in different amounts of physical education classes in higher educational institutions.The study involved first-year students in 2002, 2004, 2008 - 2010. A comparative analysis of carpal dynamometry today's students and students of 2002 and 2004. Definite difference in terms of carpal dynamometer and the power index. The dependence of the strength indicators of the number of classroom hours physical education. The study usedthe resultsof the questionnairestudentsayear of facultygovernance.